Heparin solution in the prevention of occlusions in Hickman® catheters a randomized clinical trial - Sandra Regina da Silva; Mitzy Tannia Reichembach; Letícia Pontes; Gisele de Paula e Silva Carneiro Mendes de Souza; Solena Kusma
Objective: to evaluate the effectiveness of the 50 IU/mL heparin solution compared to the 0.9% isotonic saline solution in preventing occlusion of the double lumen Hickman® catheter, 7 and 9 French, in patients undergoing hematopoietic stem cell transplantation. Method: a triple-blind randomized clinical trial. 17 double-lumen catheters (heparin group: n=7 and 0.9% isotonic saline group: n=10) were analyzed in which the two catheter routes were evaluated separately, totaling 34 lumens. The outcome variables were occlusion without reflux and complete occlusion. Descriptive analyses were performed using the Chi-square test and, of survival, according to the Kaplan-Meier test. Results: the mean number of days until the occlusion outcome was 52 in the heparin group and 13.46 in the 0.9% isotonic saline group in the white catheter route (p<0.001). In the red route, the mean follow-up days in the heparin group were 35.29, with no occlusion and 22.30 in the 0.9% isotonic saline group until the first occlusion (p=0.030). Conclusion: blocking with 50 IU/mL heparin solution is more effective than 0.9% isotonic saline in preventing occlusion of the Hickman® catheter. Brazilian Registry of Clinical Trials: RBR-3ht499.